Educational video recommender system for computer science students using content-based filtering / Walid Burhani Mohd Zamani - Mohd Zamani, Walid Burhani (2025)
This paper proposes the development of a content-based filtering educational video recommendation system that can assist and help students, particularly those studying computer science, to search for educational videos effectively and efficiently to meet their learning preferences and needs. The problem is the student finds it hard to find suitable educational videos that suit their interest, and students get time consuming when searching for educational videos. The objective is to study the content-based algorithm, to develop the prototype of educational video recommendation system using content-based filtering algorithm and to evaluate the performance and accuracy of the content-based filtering algorithm. The evaluation is very good performance which is the precision is 1.00, MAE is 0.49 and MSE is 0.26. These results validate the robustness and reliability of the algorithm, confirming its capability to provide precise and accurate recommendations, thereby fulfilling the stated objectives.